Health Promotion Development in the Spa Treatment. Perspectives for the European Countries Learned from Poland's Experiences - Woźniak-Holecka, Joanna; Romaniuk, Piotr; Holecki, Tomasz; Frączkiewicz-Wronka, Aldona; Jaruga, Sylwia (Frontiers in Pharmacology, 2017)
The main aim of the paper is to outline the perspective for future developments of the spa treatment in light of demographic transitions characterized by the increasing number of seniors, as well as changing expectations and health needs of younger population. We made a systematic review of literature referring to the experience of Poland, and similar experiences of other countries in Central Europe. Based on the existing knowledge we conclude that spa treatment should become one of the preferred directions of development of health systems in European countries. Moreover, we state that a desirable direction to modify the therapeutic paradigm used in spa treatment is to put a far-reaching greater emphasis on the provision of innovative health promotion, which is justified by both its effectiveness, and strongly good foundation for its provision in spas. For this purpose it is necessary to extend the specialized health sector personnel with qualified health educators, which will enable an effective implementation of health promotion actions and their proper alignment to the specific target groups. Developing this category of specialists will also enable other professionals to concentrate on therapeutic activity fitting their competence.